2021
DOI: 10.1177/23259671211010482
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Charges and Payments for Outpatient Arthroscopic Meniscectomy From 2005 to 2014: Hospital Reimbursement Increased Steadily as Surgeon Payments Declined

Abstract: Background: Charge and reimbursement trends for arthroscopic partial meniscectomies among orthopaedic surgeons, anesthesiologists, and hospital/surgery centers have not been formally analyzed, even though meniscectomies are the most commonly performed orthopaedic surgery. Purpose: To analyze Medicare charge and reimbursement trends for surgeons, anesthesiologists, and hospital/surgery centers for outpatient arthroscopic partial meniscectomies performed in the United States. Study Design: Economic and decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Numerous investigations demonstrated that real surgeon reimbursement has been declining over time. 6,9,10,14,18,22,27,35 LaPrade et al 14 found that surgeon reimbursement for outpatient arthroscopic meniscectomy decreased 15.5% from 2005 to 2014, while the current study demonstrated a 1.2% decline per year in surgeon reimbursement. Taken together, these findings suggest that cost-optimization strategies may be more efficacious when they are not provider-focused.…”
Section: Discussioncontrasting
confidence: 45%
“…Numerous investigations demonstrated that real surgeon reimbursement has been declining over time. 6,9,10,14,18,22,27,35 LaPrade et al 14 found that surgeon reimbursement for outpatient arthroscopic meniscectomy decreased 15.5% from 2005 to 2014, while the current study demonstrated a 1.2% decline per year in surgeon reimbursement. Taken together, these findings suggest that cost-optimization strategies may be more efficacious when they are not provider-focused.…”
Section: Discussioncontrasting
confidence: 45%
“… 26 , 27 For arthroscopic partial meniscectomy, LaPrade et al. 28 found that from 2005 to 2014, increasing hospital reimbursement outpaced declining surgeon reimbursement by 365%. They hypothesized drivers of this gap included material overhead, hospital administration, and devaluation of the CPT analyzed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The policy of paying hospitals substantially more, in some cases twice as much, for the identical services provided in an outpatient setting acts as a disincentive to pursuing innovations that shift care out of the higher-cost hospital setting, thus perpetuating inflationary cost trends and inhibiting patient access 8. These payment differentials poorly use taxpayer and beneficiary dollars while providing mega-hospital systems with the ability to acquire physician practices and promote consolidation, thereby limiting market competition and restricting treatment options for patients 9–13. As shown in Figure 1, the cost of inpatient procedures varies 3-fold across several local hospital partners within our institution, with no difference in clinical outcomes.…”
Section: Encourage Site-neutral Paymentsmentioning
confidence: 99%
“…taxpayer and beneficiary dollars while providing mega-hospital systems with the ability to acquire physician practices and promote consolidation, thereby limiting market competition and restricting treatment options for patients. [9][10][11][12][13] As shown in Figure 1, the cost of inpatient procedures varies 3-fold across several local hospital partners within our institution, with no difference in clinical outcomes.…”
mentioning
confidence: 97%